J.H. Thomas, TUC Congress, Scarborough, 1925 (1925)
1925 "J.H. Thomas, TUC Congress, Scarborough, 1925" [g0875001.jpg], 1925 James Henry Thomas (1874-1949) was born in Newport, Monmouthshire and led his first strike shortly after starting work as a engine-cleaner with the Great Western Railway in 1889. In 1898, he attended the annual conference of the Amalgamated Society of Railway Servants and was elected to various union posts, becoming assistant secretary of the newly formed National Union of Railwaymen in 1913 and General Secretary from 1917. He was TUC President in 1920. TUC Organisation